Hubungan Kadar Interleukin-10 dan Tuberkulosis Multi-Drug Resistant: [Interleukin-6 Serum Level in Multidrug-Resistant Tuberculosis] - Nurjanah Lihawa; Resti Yudhawati (Jurnal Respirasi, 2015)
Background: Prevalence of multi-drug resistant tuberculosis (MDR-TB) is increased by the time. In Indonesia, there were an  estimated 1.9% of new cases and 12% of previously treated cases. Protection against Mycobacterium tuberculosis is dependent on  Th1 cell CD4+ that produced pro-inflammatory cytokines such as IFN-γ and TNF-α. T cell regulators (Tregs) produced IL-10 as anti- inflammatory cytokine is against the function of those pro-inflammatory cytokines. It is believed that immune suppression is responsible  for MDR-TB. The previous study showed impaired Th1 responses and enhanced regulatory T-cell levels in circulatory blood of MDR- TB patients. The study of IL-10 represented anti-inflammation cytokine as immune suppression never been conducted in Indonesia.  Objective: To analyze relationship between level of interleukin-10 and Multi-drug resistant tuberculosis. Methods: The study was  conducted at the outpatient department of MDR-TB and DOTS of Dr. Soetomo hospital in Surabaya. Total sample was 38 of TB patients  that consist of 19 MDR-TB patients (secondary resistant) and 19 non-MDR TB patients as control. Results: In this study we found that  the median level of IL-10 as 5.7±3.3 pg/mL in the group of MDR-TB patients with minimum level was 1.3 pg/mL and maximum level  was 14.0 pg/mL while median level of IL-10 in non-MDR TB patients was 7.0±3.4 pg/mL with 3.2 pg/mL and 16.5 pg/mL, respectively.  To analyze correlation between time to first of having TB until became MDR-TB and level of IL-10 by using Pearson’s correlation, we  showed that no statistical correlation (p>0.05). According to statistical classification, we found that no statistical correlation between  level of IL-10 and the history of treatment in MDR-TB patients (p>0.05). Data showed that all the history of treatment classification  dominated by MDR-TB patients with the low level of IL-10. We also found that no statistical difference with the level of IL-10 in MDR- TB and non-MDR TB patients (p>0.05) although in descriptive state we found the level of IL-10 was higher in non-MDR TB patients.  And also there was no relationship between level of IL-10 and MDR-TB (p>0.05). It could be explained that the host factor was not  involved and in the other side we still not known the factor of agents, yet. The low level of IL-10 that was observed in this study could be  interfering by the strain of M.tb which not assessed in this study. Conclusion: In this study we found that level of IL-10 is not increase  in MDR-TB patients and there was no relationship between level of IL-10 and MDR-TB (p>0.05).